Implementation of Load Balancing Using PCC (Per-Connection Classifier) Method with Failover Based on MikroTik Router (Case Study at RSUD Siti Fatimah) - Pratama, Muhammad Bobby; Mirza, A. Haidar; Suryayusra; Mukti, Aan Restu (PT ARRUS Intelektual Indonesia, 2024)
The rapid advancement of information technology, particularly in computer networking, has played a crucial role in supporting the operations of various institutions, including hospitals. RSUD Siti Fatimah is one such institution that leverages computer network technology to enhance performance and the quality of patient care. However, the hospital faces challenges with congested and slow network connections, which can hinder operational efficiency. To address this issue, a load balancing solution based on MikroTik was implemented using the Per-Connection Classifier (PCC) method, allowing the distribution of load across two ISPs for a more stable and faster connection. The PCC method was chosen for its ability to enhance connection speed and distribute network load evenly between the two gateways, thereby preventing overload. Additionally, a failover technique was applied to ensure that if one ISP connection fails, the network traffic is automatically switched to the other ISP, keeping the network operational without interruption. The implementation of this solution is expected to improve network efficiency and enhance healthcare services at RSUD Siti Fatimah.